Sexually transmitted infections during pregnancy and subsequent risk of stillbirth and infant mortality in Kenya: a prospective study. (18th September 2018) - Warr, Alex J; Pintye, Jillian; Kinuthia, John; Drake, Alison L; Unger, Jennifer A; McClelland, R Scott; Matemo, Daniel; Osborn, Lusi; John-Stewart, Grace
Abstract : Objectives: We evaluated the relationship of sexually transmitted infections (STIs) and genital infections during pregnancy and subsequent risk for infant mortality and stillbirth. Methods: This was a nested longitudinal analysis using data from a study of peripartum HIV acquisition in Kenya. In the parent study, HIV-uninfected women were enrolled during pregnancy and followed until 9 months postpartum. For this analysis, women who tested positive for HIV at any point, had a non-singleton pregnancy or a spontaneous abortion <20 weeks were excluded. At enrolment, laboratory methods were used to screen for bacterial vaginosis (BV), vaginal yeast, Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Trichomonas vaginalis (TV). Syphilis was diagnosed using rapid plasma reagin testing and genital ulcer disease (GUD) identified by clinical examination. Treatment of laboratory-confirmed STIs and syndromic management was provided per Kenyan national guidelines. Predictors of stillbirth and infant mortality were determined using logistic regression and Cox proportional hazards models. Results: Overall, among 1221 women, 55% had STIs or genital infections detected: vaginal yeast (25%), BV (22%), TV (6%), CT (5%), NG (2%) and syphilis (1%). Among women with STIs/genital infections (n=592), 34% had symptoms. Overall, 19/1221 (2%) women experienced stillbirths. Among 1202 live births, 34 infant deaths occurred (incidence 4.0 deaths per 100 person-years, 95% CI 2.8 to 5.5). After adjustment for maternal age, education and study site, stillbirth was associated with maternal GUD (adjusted OR=9.19, 95% CI1.91 to 44.35, p=0.006). Maternal NG was associated with infant mortality (adjusted HR=3.83, 95% CI1.16 to 12.68, p=0.028); there was some evidence that maternal CT was associated with infant mortality. Stillbirth or infant mortality were not associated with other genital infections. Conclusions: STIs and genital infections were common, frequently asymptomatic and some associated with stillbirth or infant mortality. Expediting diagnosis and treatment of STIs in pregnancy may improve infant outcomes.